Development of Interactive Learning Media Based on Genially for Informatics Subject in Grade X of Vocational High School - Nurajizah, Nija; Habibie, Alfadl; Muhammad, Taofik (Design Journal, 2025)
This study developed interactive Genially-based learning media for Grade X vocational Informatics focusing on network hardware. The development followed an R&D approach structured with the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. During the analysis stage, teacher‑centered delivery and low student autonomy were identified as barriers to engagement. The design phase produced a storyboard specifying navigation flow, visual layout, and embedded quiz checkpoints. The media was then built in Genially and reviewed by a subject expert and a media expert. Validation used a 5-point Likert instrument covering accuracy, curriculum alignment, clarity, usability, visual layout, responsiveness, and interaction. The subject expert awarded a score equivalent to 100%, and the media expert 90%, both classified as very feasible under the predefined criteria. Implementation involved 20 students in the Computer and Network Engineering track at SMK Islam Tenjonagara, who accessed the material individually and completed a response questionnaire. Aggregate student feedback reached 83.8%, categorized as very good, indicating positive perceptions of clarity, ease of navigation, and usefulness for self‑paced review. The findings support adoption of the Genially-based media as a supplementary resource for Grade X network hardware instruction in vocational settings and justify further refinement toward learning gain measurement.